ANALISIS OPEN GOVERNMENT PADA DIREKTORAT JENDEREAL ENERGI BARU, TERBARUKAN DAN KONSERVASI ENERGI, KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL REPUBLIK INDONESIA - Anggraeni Respitawulan (NATAPRAJA, 2019)
The change paradign in energy demand side and supply side management make goverment should think creatively to increase nergy national mix 23% at 2025 with new and renewable energy development programme. This research aims to describe the open goverment strategy condition in new and renewable energy development programme use kualitatif method through interview and observation. In general pelaksaan open government have on the directorate general ebtke has been implemented in terms of planning, implementation and supervision activities. This reseach find that new and renewable energy programme basically has a good platform, proven from a lot of using information and technology to support the programme.  But unfortunately many platform are not used optimally to increase tranparency, participation and collaboration as a open goverment theory to the new and renenwable energy programme. In the transparency aspect informatio technology has used to broadcast information, in participation aspect, public has no access to policy formulation. While in the collaboration aspect show with many cooperation between goverment, private sector, public, NGO and other institution or country in various new and renewable energy programme.